Oesophageal mesenchymal tumours: clinicopathological features and absence of Epstein-Barr virus. - Lam, K Y (1999)
BACKGROUND: Recent studies have suggested that the Epstein-Barr virus (EBV) is associated with smooth muscle tumours (leiomyoma and leiomyosarcoma) in patients with human immunodeficiency virus and in organ transplant recipients. Leiomyoma is the most common mensenchymal tumour found in the oesophagus. AIM: To report a single institution experience on oesophageal mesenchymal tumours and to determine whether EBV is associated with these tumours. METHODS: 40 sporadic oesophageal mesenchymal tumours were studied and their diagnosis confirmed on pathological review and immunohistochemical studies. Formalin fixed, paraffin was embedded tissues from these tumours were analysed for EBV using in situ hybridisation for two messenger RNA (mRNA) probes, EBER and BamH1 W. RESULTS: The oesophageal mesenchymal tumours comprised 36 leiomyomas, two undifferentiated stromal tumours, and two gastrointestinal autonomic nerve tumours (GANTs). Median age of the patients with leiomyoma (26 men, 10 women) was 62 years (range 30 to 85) and 81% of them had an asymptomatic lesion. The median longitudinal size was 1.2 cm. Multiple leiomyomas were seen in 11% of the patients and calcification was noted in one tumour. Coexisting squamous cell carcinoma was found in one third of cases. The stromal tumours were small, asymptomatic, and located in the lower third of the oesophagus, while the GANTs were large, symptomatic, and found in the upper third of the oesophagus. EBV mRNAs were not detected in all these tumours. CONCLUSIONS: The clinicopathological features of oesophageal leiomyoma, undifferentiated stromal tumour, and GANT were different. Some oesophageal leiomyomas were associated with oesophageal squamous cell carcinomas. EBV is not associated with sporadic oesophageal mesenchymal tumours.